ALL THE NEW IS THE WELL FORGOTTEN OLD: AUTOPERICARDIAL MITRAL ANNULOPLASTY FOR DEGENERATIVE DEFECTS - S.A. ZHURKO; A.B. GAMZAEV; K.M. AMINOV; P.V. PIMENOVA (Avicenna Tajik State Medical University, 2021)
Objective: To present the first-hand results of a modified mitral annuloplasty (MA) with an autopericardial strip (APS) in degenerative mitral valve disease (DMVD). Methods: Fifty-three patients with DMVD (mean age, 54.9±9.5 years (36-78 years); n=32 men (60.4%) and n=21women (39.6%)) undergoing MA with an APS, between January 2017 and January 2020 were retrospectively studied. In the overwhelming majority of cases, triangular and quadrangular resections of the P2 segment were performed. In addition, in some cases, neochords were implanted to the A2 segment. Intraoperatively, the result of MA was considered satisfactory if, according to transoesophageal echocardiography, the degree of mitral regurgitation (MR) did not exceed grade 1. Results: No in-hospital mortality was observed. One female patient had an early relapse caused by the rupture of one of the neochords at the A2 segment. However, the MR did not exceed grade 2, and the patient was actively followed up. Conclusion: Individual APS length selection avoids overcorrecting and achieves adequate systolic and diastolic mitral valve performance.